2014
DOI: 10.3892/mmr.2014.2133
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal administration of the globular adiponectin gene ameliorates diabetic nephropathy in Wistar rats

Abstract: The present study investigated the potential effects of the long-term expression of exogenous adiponectin (ADPN) on normal and diabetic kidneys. Type 2 diabetes mellitus models were induced by high-lipid and high-sucrose feeding plus intraperitoneal injection of streptozotocin. The recombinant plasmid pIRES2-EGFP-gAd, which is able to co-express globular ADPN (gAd) and enhanced green fluorescent protein (EGFP), was intraperitoneally injected into rat models mediated by Lipofectamine. In total, 32 Wistar rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In contrast to the case of adiponectin deficiency, administration of adiponectin has been reported to improve podocyte permeability to albumin through the inhibition of NADPH oxidase activity [20]. Intraperitoneal infusion of adiponectin has also been shown to decrease renal TGF-b expression and improve mesangial expansion in the kidneys of diabetic rats [21]. Furthermore, in an obese African-American population, there was a significant and inverse correlation between plasma adiponectin concentration and UAE values [20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the case of adiponectin deficiency, administration of adiponectin has been reported to improve podocyte permeability to albumin through the inhibition of NADPH oxidase activity [20]. Intraperitoneal infusion of adiponectin has also been shown to decrease renal TGF-b expression and improve mesangial expansion in the kidneys of diabetic rats [21]. Furthermore, in an obese African-American population, there was a significant and inverse correlation between plasma adiponectin concentration and UAE values [20].…”
Section: Discussionmentioning
confidence: 99%
“…Serum APN levels in type 1 diabetes positively correlate with plasma total antioxidant status[70]. Increased APN levels are associated with less renal disease[71], suggesting possible protective effects of APN with respect to other type 1 diabetes complications including diabetic retinopathy. In type 2 diabetic patients, circulating APN levels are positively correlated with retinal blood flow in male patients with early-phase diabetic retinopathy, possibly through increased blood velocity and dilated vessels[5].…”
Section: Apn In Retinal Metabolic Diseasesmentioning
confidence: 99%
“…Multiple interventional studies in rodent models of diabetic kidney disease have suggested the potential benefits of activating AMPK for DN. Many of these studies used activators of AMPK that also have AMPK-independent activities, which could impact kidney function autonomously or nonautonomously and are limited in their capacity to activate AMPK at clinically relevant doses (Lee et al, 2007;Sharma et al, 2008;Dugan et al, 2013;Kim et al, 2013;Yuan et al, 2014). Therefore, we set out to identify novel, specific, small molecule activators of AMPK that hold the potential for clinical development as a treatment option for DN.…”
Section: Introductionmentioning
confidence: 99%